A STUDY OF CONTEXT PROBLEMS IN MULTIPLICATIVE FIELD EXPLOITED BY TEACHERS AND STUDENTS OF ELEMENTARY EDUCATION - Cardoso, Valdinei Cezar; Amaral-Schio, Rubia Barcelos [UNESP]; Oliveira, Samuel Rocha de (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
This article tries to discuss different strategies adopted by students and teachers of the Initial Years of Elementary Education in solving three problems of the multiplicative conceptual field, in order to understand some problems and features in the cognitive structuring of fundamental concepts of Mathematics. During a national program of continuing teacher training, we applied a questionnaire as a data collection instrument. The analysis shows that the teachers involved in the research did not present difficulties to solve the proposed problems, which is a good indicator that they have effective schemes for solving problems situations in this conceptual field. On the other hand, many students presented difficulties in solving the same problems, especially those involving non-integer numbers (a subject not yet studied by all the students), some also because of difficulties in reading and interpreting the statements, and others because they did not verify if results satisfied the proposed question. Some errors provide evidence that students have not developed reasoning strategies in the multiplicative conceptual field and thus do not have effective schemes for solving the proposed problems. Other manifestations in the solutions also point to conceptual misunderstandings that must be understood by researchers and teachers, in the sense of developing actions that seek to overcome them.
Keywords: Pro-Letramento; Elementary School; Mathematical Education; Conceptual Field Theory; Multiplication Problems